Contagious switching. (21st September 2021) - Owyang, Michael T.; Piger, Jeremy; Soques, Daniel
Summary: We analyze the propagation of recessions across countries using a model with multiple qualitative state variables in a vector autoregression (VAR). The VAR may include country‐level variables to determine whether policy also propagates across countries. We consider versions of the model with observed discrete states or unobserved discrete states, where the latter is inferred from fluctuations in economic data. We apply the model to Canada, Mexico, and the United States to test if spillover effects were similar before and after the North American Free Trade Agreement (NAFTA). We find that trade liberalization increased business cycle propagation across the three countries.